EVALUATING THE IMPACT OF INFORMATION, EDUCATION, AND COMMUNICATION INITIATIVES ON MENSTRUAL HYGIENE PRACTICES AMONG ADOLESCENT GIRLS AGED 13-17: A RANDOMIZED CONTROL TRIAL - Pallavi,; Jha, Milind (Student's Journal of Health Research Africa, 2024)
Background Adolescent girls' health, dignity, and general well-being depend heavily on menstrual hygiene management (MHM). Inadequate MHM practices have been connected to social problems including school absenteeism and health hazards like reproductive tract infections. The study evaluated how information, education, and communication (IEC) activities affected the menstrual hygiene practices of teenage females between the ages of 13 and 17. Methods A study was conducted over 6 months, with 400 adolescent girls (240 school-going and 160 out-of-school) participating. Data were collected through a predesigned, semi-structured questionnaire in the pre-and post-intervention phases. The IEC sessions focused on MHM, using visual aids and group discussions. Statistical analysis was performed using the chi-square test to determine significant changes in behavior. Results Before the intervention, only 45% of the participants used sanitary pads, while 55% used cloth. Post-intervention, the use of sanitary pads increased to 75%. The frequency of changing menstrual products also improved, with 70% of participants adopting the practice of changing products more than three times per day, compared to 35% pre-intervention. Handwashing with soap after changing menstrual products increased from 30% to 77.5%, and awareness of the menstrual cycle rose from 25% to 80%. All changes were statistically significant (p < 0.001). Conclusion The IEC intervention led to substantial improvements in menstrual hygiene practices and knowledge among adolescent girls. The study demonstrates that health education initiatives can significantly improve menstrual hygiene behavior, especially in resource-limited settings. Recommendations Future efforts should focus on scaling similar educational programs in other rural areas, improving access to affordable menstrual products, and ensuring the availability of water and sanitation facilities in schools and communities.